2015
DOI: 10.3928/23258160-20150909-03
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography of Diabetic Retinopathy in Human Subjects

Abstract: OCTA generates high-resolution angiograms that illustrate many of the clinically relevant findings in diabetic retinopathy and offers a novel complement or alternative to fluorescein angiography. Although currently an investigational technique, OCTA in combination with standard OCT imaging is at least as good as fluorescein angiography in the evaluation of the macular complications of diabetic retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
146
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(161 citation statements)
references
References 17 publications
11
146
0
4
Order By: Relevance
“…As we and others previously demonstrated, [19][20][21][22][23][24] en face OCT angiography can directly visualize well-delineated microvascular structures of new vessels and differentiate them from original retinal vascular structures. However, the detailed morphologic features of these newly formed vessels have not been extensively characterized.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…As we and others previously demonstrated, [19][20][21][22][23][24] en face OCT angiography can directly visualize well-delineated microvascular structures of new vessels and differentiate them from original retinal vascular structures. However, the detailed morphologic features of these newly formed vessels have not been extensively characterized.…”
Section: Discussionmentioning
confidence: 65%
“…Several authors have clearly shown neovascularization in PDR using en face OCT angiography. [19][20][21][22][23] We also recently reported the regression and pruning of NVD with remarkably proliferative microvessels following the intravitreous injection of anti-VEGF. 24 Spaide 25 described the signs of vascular abnormalities in CNV after anti-VEGF therapy observed by OCT angiography; however, morphologic assessment of neovascularization in PDR remains to be elucidated.…”
mentioning
confidence: 89%
“…The advent of OCTA analysis can provide high resolution images that allow the visualization of morphologic microvascular abnormalities, 19,20,[27][28][29] and also are well-suited to mathematical analysis of each vascular layer. Optical coherence tomography angiography parameters that have been reliably quantified in diabetic patients include the foveal avascular zone (FAZ), area of nonperfusion, and perfusion density.…”
Section: Discussionmentioning
confidence: 99%
“…Further work on a larger subset of diabetic patients (with age-matched controls), as well as application to threedimensional reconstructions of OCTA and other imaging modalities, may reveal further insights. 27,36 We believe that fractal analysis is a clinically useful tool that may help guide follow-up and treatment for patients with more severe disease who are at greater risk of progression to proliferative disease or DME.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] When compared with fluorescein angiography (FA), OCTA can image many microvascular changes more readily due to its higher resolution as well as less obscuration from fluorescein dye with the exception of microaneurysms where the pooling of dye on FA make these more apparent. [38][39][40] The normally ovoid and regular shape of a normal FAZ may become irregular and enlarged in DR, which is more notable in the deep inner retina. 41 The FAZ is enlarged in diabetic eyes compared with age-matched controls, and increases with each stage of progression of retinopathy.…”
Section: Diabetic Retinopathymentioning
confidence: 99%